Patient‐reported fatigue refines prognosis in higher‐risk myelodysplastic syndromes (MDS): a MDS‐CAN study. (31st May 2021) - Amitai, Irina; Geddes, Michelle; Zhu, Nancy; Keating, Mary‐Margaret; Sabloff, Mitchell; Christou, Grace; Leber, Brian; Khalaf, Dina; Leitch, Heather A.; St‐Hilaire, Eve; Finn, Nicholas; Shamy, April; et al.
Summary: The incorporation of patient‐reported outcomes with traditional disease risk classification was found to strengthen survival prediction in patients with myelodysplastic syndromes (MDS). In the present Canadian MDS registry analysis, we validate a recently reported prognostic model, the Fatigue‐International Prognostic Scoring System among higher‐risk patients [FA‐IPSS(h)], which incorporates patients' reported fatigue, assessed by the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life‐Core 30 (QLQ‐C30), with a threshold of ≥45 points, in higher IPSS score, stratifying them into distinct subgroups with different survival outcomes. We further validated this concept, using the Revised IPSS >3·5 as cut‐off for the definition of higher‐risk MDS, and patients' reported fatigue according to Edmonton Symptom Self‐Assessment Scale (ESAS) Global Fatigue Scale (GFS), a single‐item fatigue rating scale, which is easier to deploy. This emphasises the power of self‐reported fatigue at refining overall survival predictions in higher‐risk MDS and further bolsters the importance of considering patient‐related outcomes in global assessments.